circDENND4C serves as a sponge for miR-200b to drive non-small cell lung cancer advancement by regulating MMP-9 expression - Lv, Yaming; Wang, Lan; Zhang, Yunhui; Wei, Dong; Hu, Yajie (Frontiers in Oncology, 2025)
IntroductionLung cancer has a higher incidence and mortality rate than other cancers, especially non-small cell lung cancer (NSCLC), accounting for 85% of the cases. The role of the circDENND4C/miR-200b/matrix metalloproteinase-9 (MMP-9) regulatory axis in NSCLC remains largely unknown.MethodsNSCLC cell lines were used to examine the expression of circDENND4C, miR-200b, and MMP-9 via qRT-PCR or Western blot. The target relationship of circDENND4C, miR-200b, and MMP-9 was examined by RNA fluorescence in situ hybridization (RNA-FISH), immunofluorescence (IF), dual-luciferase reporter system, quantitative real-time polymerase chain reaction (qRT-PCR), and Western blot. Then, a cell count kit-8 (CCK-8) experiment, flow cytometry, and migration/invasion assays were performed to assess the biological function of circDENND4C, miR-200b, and MMP-9 by transfecting with their overexpression or knockout plasmids in A549 cells. Finally, the proteins related to cell adhesion and tight junction were further tested by Western blot and IF.ResultscircDENND4C and MMP-9 were found to be highly expressed in NSCLC cell lines, while miR-200b was lowly expressed in NSCLC cell lines. Moreover, circDENND4C could sponge miR-200b to target MMP-9. Subsequently, it was observed that knockdown of circDENND4C and MMP-9 or the upregulation of miR-200b repressed cell proliferation and cell cycle progression, increased cell apoptosis, and hindered cell migration and invasion. Finally, it was also found that the circDENND4C/miR-200b/MMP-9 regulatory axis might be involved with cell adhesion and tight junction to influence tumor metastasis.ConclusionsAltogether, our study reveals a novel regulatory loop in which the circDENND4C/miR-200b/MMP-9 axis may modulate NSCLC progression, indicating potential biomarkers for the diagnosis or treatment of NSCLC.